Rancang Bangun Aplikasi Pengendalian Persediaan pada Apotek 178 - Lidya Ike Patricia; Arifin Puji Widodo; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Abstract: 178 pharmacies founded by Mrs. Lusi August 2013. The pharmacy is located at No. 178 Jalan Surabaya East Ploso. At this time, 178 pharmacies to check the card stock, if the stock exists then checks completed but if the stock is empty then the pharmacy will make a reservation by making a memorandum of reservations that will be given to the supplier. Supplier will make the process of creating a memorandum of expenditure which will be given to the pharmacy as proof of purchase along with the drugs ordered by the pharmacy. Based on data from 178 pharmacy expenditure in the period June, July and August 2014, there are number of drugs with an empty stock reached 45%. From these percentages outlined that for high spending levels (≥ 70%) with 34% the amount of medication with an empty stock, while the expenditure level moderate (<70%) are 11% the amount of medication with an empty stock.According to this problem, then the solution is to make the design of the application of medicines in pharmacies 178 using ABC analysis, ROP (Reorder Point) combined with less safety stock and lead time. Doing so can help the pharmacy to pharmacy owners can assist in controlling the drug supply in the display or in storage. As well as 178 pharmacies can help owners in decision making for the future development of the pharmacy business processes.From the test results and evaluation system that has been created it can be concluded from the Application Inventory Control at Pharmacy 178 is the application can generate output reports ABC classification and reporting of inventory control to help the pharmacy in addressing the problem of shortage of stocks which contributed to the decline. The report formed also can help the pharmacy to do scheduling. This application also generates reports to provide information to managers such as reception reports per period, per period expense reports, inventory reports per period, and report expired.